The Reality of Parents Communicating with the School to Raise their Children's Academic Achievement from the Point View of Principals and Teachers of the Northwest Badia Schools - Alhamdi, Hana' Salameh Salem (Journal of Educational and Psychological Sciences, 2021)
The study aimed to identify The Impact of Parents Communicating with the School in Order to Raise their Children's Academic Achievement from the Point View of   Principals and Teachers of the Northwest Badia Schools, and to identify the difference between the estimates of the study sample individuals in the reality of parents ’contact with the school in order to raise their children's academic achievement in the northwestern Badia schools depending on the variable (Gender), the study course consisted of (175) principals and teachers from public schools affiliated to the Directorate of Education in the Northwestern Badia, and the study used the descriptive survey approach, and the results showed that the reality of parents communicating with the school in order to raise their children's academic achievement in the Northwest Badia schools It came with a medium evaluation score from the point of view of principals and teachers, and it also showed no statistically significant differences in the reality of parents' communication with the school in order to raise their children's academic achievement in the northwestern Badia schools according to the variable (gender). The communication used and the organization of workshops about communication and its importance for managers, teachers and educational supervisors in the Ministry of Education, and the necessity of Teachers' possession of life skills that enhance communication skills and human standards while interacting with students.
Keywords: Communication; Parents; Northwestern Badia Schools